ANALISIS KEAKTIFAN PEMBELAJARAN KIMIA MENGGUNAKAN MEDIA GOOGLE CLASSROOM PADA MASA PANDEMI COVID-19 KELAS X MIA DI SMA NEGERI 2 SIBOLGA - Dame Hotmauli Sihombing; Nenni Faridah Lubis; Emmi Juwita Siregar (Program Studi Pendidikan Matematika Institut Pendidikan Tapanuli Selatan, 2021)
Abstract. The study aims to analyze the activeness of learning Chemistry using Google Classroom , during the COVID-19 Pandemic, class X MIA at SMA Negeri 2 Sibolga. This type of research is a qualitative descriptive study. The population of this study were students of class X MIA at SMA Negeri 2 Sibolga, whitch consisted of sis classes with a amount of one hundred ninety-six students and sample of thirty-six students. The sample collection technique used was purposive sampling. The instruments used were questionnaires and interview data analysis techniques in the from of data reduction,data presentation, and data verification. The results of the questionnaire on the students Chemistry learning activeness using Google Classroom media were 74,44%, and they were in the “good” category. This is because the students are active in learning Chemistry using Google Classroom media, which is 81,67%, whitch is in the “very good” category. The convenience aspects of Google Classroom were found to be 63,33%, included in the “sufficient” category. The service quality aspects of Google Classroom were obtained 74,44% were in the “good” category. Finally , the effectiveness aspect of Google Classroom is found to be 78,33% in the “good” category. While the result of an interview given to one of the Chemistry teachers at SMA Negeri 2 Sibolga. Were contradictory to the results of a questionnaire given to students to understand Chemistry. Because Chemistry lessons are starting to be studied and accepted in the first grade of high school, and now learning is carried out online using the internet network, for that students find if difficult to do learning, So this causes Chemistry learning to be less effective to understand trough Google Classroom. Keywords: Analysis, Chemistry Learning and Google Classroom.